Increasing Use of Mammography Among Older, Rural African American Women: Results From a Community Trial - Earp, Jo Anne; Eng, Eugenia; O'Malley, Michael S.; Altpeter, Mary; Rauscher, Garth; Mayne, Linda; Mathews, Holly F.; Lynch, Kathy S.; Qaqish, Bahjat (East Carolina University, 2002)
Objectives. A community trial was undertaken to evaluate the effectiveness of the North Carolina Breast Cancer Screening Program, a lay health advisor network intervention intended to increase screening among rural African American women 50 years and older. Methods. A stratified random sample of 801 African American women completed baseline (1993–1994) and follow-up (1996–1997) surveys. The primary outcome was self-reported mammography use in the previous 2 years. Results. The intervention was associated with an overall 6 percentage point increase (95% confidence interval [CI] =−1, 14) in communitywide mammography use. Low-income women in intervention counties showed an 11 percentage point increase (95% CI = 2, 21) in use above that exhibited by lowincome women in comparison counties. Adjustment for potentially confounding characteristics did not change the results. Conclusions. A lay health advisor intervention appears to be an effective public health approach to increasing use of screening mammography among low-income, rural populations. Originally published American Journal of Public Health, Vol. 92, No. 4, Apr 2002
Keywords: Mammography use; Rural communities; Health advisor network intervention